Current state and new aspects of fertility preservation surgery in some oncogynaecological diseases - Kornovski, Yavor; Ivanova, Yonka; Kostov, Stoyan; Slavchev, Stanislav; Yordanov, Angel (Medical Studies/Studia Medyczne, 2021)
Preservation of reproductive function in young patients with uncompleted or unrealized reproductive plans in some malignant tumours of the female reproductive system has been a subject of study for many years, especially with the advances in assisted reproductive technologies. The main neoplasms that affect women in childbearing age are cervical cancer and ovarian tumours. In the current survey the novelties in the literature will be presented regarding the fertility preservation surgery in cervical cancer with size of tumour between 2 and 4 cm, granulosa cell ovarian tumours, and epithelial borderline ovarian tumours